PANTULAN (REFLEKS) PROTO AUSTRONESIA (PAN) KE PROTOBAHASA KABOLA, PROTOBAHASA HAMAP, DAN PROTOBAHASA KLON DI PULAU ALOR, NUSA TENGGARA TIMUR - Ida Ayu Iran Adhiti (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2017)
[Title: The reflexion of proto Austronesia to Kabola, Hamap, and Klon protolanguage in Alor Island, Nusa Tenggara Timur] Making data of the local languages in Nusa Tenggara Timur need to be observed, especially the local languages in Alor Island. The observer analyses the data collection in the languages of Kabola, Hamap, and Klon by the study of comparative historic linguistic.This observation uses synchronous approach, to know the language development in a period. This study is based on the result of PAN reconstruction of experts, such as: Demwolff, Dyen, Blust, Lopez, compiled by the list of Austronesia reconstruction composed by Wurm and Wilson. Comparative method used in this observation is sin comparative, to find the characteristics of similarity and the difference between relative languages that are alive in the same period. The language phenomena that is analysed is descriptive, firstly the data that is collected is the data of nowdays period. Reflection of PAN to Protolanguage Kabola, Hamap, and Klon (PKbHpKl) are found reflection of vocal phoneme PAN, vocal series of PAN, consonant phoneme of PAN, and cluster of consonant PAN on PKbHpKl. Some phonemes are reflected from Proto PAN to Protolanguage Kabola, Hamap, and Klon show that the three languages are derivativeof Proto PAN and Austronesia.